Public Key Infrastructures, Services and Applications 10th European Workshop, EuroPKI 2013, Egham, UK, September 12-13, 2013, Revised Selected Papers - Katsikas, Sokratis; Agudo, Isaac; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th European Workshop, EuroPKI 2013, held in Egham, UK, in September 2013. The 11 revised full papers presented together with 1 invited talk were carefully selected from 20 submissions. The papers are organized in topical sections such as authorization and delegation, certificates management, cross certification, interoperability, key management, legal issues, long-time archiving, timestamping, trust management, trusted computing, ubiquitous scenarios, and Web services security.
Partial Model Checking for the Verification and Synthesis of Secure Service Compositions -- Efficient and Perfectly Unlinkable Sanitizable Signatures without Group Signatures -- Revocation and Non-repudiation: When the First Destroys the Latter -- New Results for the Practical Use of Range Proofs -- STUNT: A Simple, Transparent, User-Centered Network of Trust -- What Public Keys Can Do for 3-Party, Password-Authenticated Key Exchange -- Towards a More Secure and Scalable Verifying PKI of eMRTD -- Mutual Restricted Identification -- Trust Views for the Web PKI -- A User-Centric Digital Signature Scheme -- A Test-Bed for Intrusion Detection Systems Results Post-processing -- Uncertainty in Intrusion Detection Signaling Games.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Computers and Society; Systems and Data Security